Efektivitas Komunikasi Perbankan Digital BCA KCU Tegal melalui Mesin CS Digital - Dearmauli .S, Mirari Gracea; Permadi, Didi; Edy, Sarwo (CV. ITTC INDONESIA, 2026)
This study examines the effectiveness of digital banking communication through the use of the CS Digital Machine at BCA KCU Tegal. The research problem focuses on how service messages delivered through the CS Digital Machine are understood, accepted, and utilized effectively by customers. The purpose of this study is to analyze the effectiveness of digital banking communication through the CS Digital Machine by referring to the communication effectiveness theory proposed by Tubbs and Moss, which is operationalized into indicators of information clarity, message accuracy, ease of interaction, and customer satisfaction. This research employs a descriptive qualitative approach with a case study design. Research data were obtained through semi-structured interviews with 10 informants, consisting of customers who use the CS Digital Machine and customer service staff at BCA KCU Tegal. Data analysis was conducted qualitatively through stages of data reduction, data presentation, and conclusion drawing based on interview results. The findings indicate that, based on the experiences and assessments of the informants, communication through the CS Digital Machine is considered effective, as reflected in the clarity of information that is easy to understand, the accuracy of messages in meeting service needs, the ease of interaction between customers and the machine, and the emergence of satisfaction with the service outcomes received. This study offers a perspective on digital service communication from the standpoint of communication effectiveness.